Drone-Informed Smart City Planning for Sustainable Urban River Corridors - Wikantiyoso, Respati; Aini, Nurul; Tutuko, Pindo; Tutuko, Dara Citra Saraswati (Proceedings of International Conference of Graduate School on Sustainability, 2026)
Urban riverbanks in rapidly developing cities face significant challenges, including land scarcity, informal settlements, and environmental degradation. This study explores integrating drone-based mapping, geospatial analysis, and smart environmental governance to regenerate the Brantas River corridor in Malang, Indonesia. High-resolution imagery captured using the DJI L1D-20c sensor produced orthomosaics and Digital Surface Models (DSMs), revealing substantial discrepancies between planned and actual land use. More than 60% of the riverbank was occupied by informal housing, and vegetation cover was reduced to below 20% of the designated green buffer. By overlaying drone outputs with thematic GIS data, the study identified priority areas for substituting green spaces and ecological restoration. The findings informed the development of a Management Information System (MIS) aligned with Indonesia’s One Map Policy and Satu Data Indonesia initiative, facilitating real-time monitoring and data transparency. A pentahelix collaboration model, involving government, academia, industry, community, and media, was applied to enhance participatory governance and ensure inclusivity in planning outcomes. The resulting Smart River Regeneration Framework integrates three interrelated layers: ecological restoration, spatial–architectural restructuring, and digital governance. This integrative approach demonstrates how drone and smart city technologies can support evidence-based decision-making, adaptive design, and community empowerment. Overall, the study presents a replicable model for environmentally intelligent and socially inclusive urban transformation in riverine contexts of developing cities.